On the Circulation and Thermohaline Properties of the Eastern Mediterranean Sea - Menna, Milena; Gerin, Riccardo; Notarstefano, Giulio; Mauri, Elena; Bussani, Antonio; Pacciaroni, Massimo; Poulain, Pierre-Marie (Frontiers in Marine Science, 2021)
The circulation of the Eastern Mediterranean Sea is characterized by numerous recurrent or permanent anticyclonic structures, which modulate the pathway of the main currents and the exchange of the water masses in the basin. This work aims to describe the main circulation structures and thermohaline properties of the Eastern Mediterranean with particular focus on two anticyclones, the Pelops and the Cyprus gyres, using in-situ (drifters and Argo floats) and satellite (altimetry) data. The Pelops gyre is involved in the circulation and exchange of Levantine origin surface and intermediate waters and in their flow toward the Ionian and the Adriatic Sea. The Cyprus Gyre presents a marked interannual variability related to the presence/absence of waters of Atlantic origin in its interior. These anticyclones are characterized by double diffusive instability and winter mixing phenomena driven by salty surface waters of Levantine origin. Conditions for the salt finger regime occur steadily and dominantly within the Eastern Mediterranean anticyclones. The winter mixing is usually observed in December–January, characterized by instability conditions in the water column, a gradual deepening of the mixed layer depth and the consequent downward doming of the isohalines. The mixing generally involves the first 200 m of the water column (but occasionally can affect also the intermediate layer) forming a water mass with well-defined thermohaline characteristics. Conditions for salt fingers also occur during mixing events in the layer below the mixed layer.